Essay, otherness and experience: the literary writing at school - Raquel Leão Luz; Rosa Maria Bueno Fischer (Universidade Federal de Santa Catarina, 2019)
The subject of this article is literary writing at school. We establish a discussion from the connections between the narrative creation process with the topics of essay, experience and otherness. We intend to propose, drawing from authors like Foucault, Deleuze, Skliar and Agamben, how different experimentations with literature can work in order to refine teachers and students daily writing process. A short story written by a middle school student is the focal point of our analyses, and its philosophical perspective offers ideas on how to sever from standard and more instrumental writing methods, towards further possible ways to engage literature and writing considering a school environment.